Direct measurement of the male recombination fraction in the human beta-globin hot spot. - Schneider, J; Peto, T; Boone, R; Boyce, A; Clegg, J (2002)
Recombination was measured across nine intervals in the human beta-globin gene cluster by single-sperm analysis. A recombination fraction of approximately 0.9% was calculated across an approximately 11 kb region using a new method to estimate recombination fractions from single-sperm typing data. No recombination was detected in an adjacent approximately 90 kb region that extends upstream of the beta-globin cluster. These data are consistent with previous estimates based on population genetic analysis, and suggest a recombination rate of nearly two orders of magnitude greater than the genome average of approximately 1 cM/Mb. Because recombination hot spots will destroy linkage disequilibrium across small physical regions, knowledge about the location and strength of such hot spots could be extremely valuable for genetic association studies.